PENGEMBANGAN KARTU PETUALANGAN SEBAGAI MEDIA PROMOSI KESEHATAN UNTUK MENINGKATKAN KEDISIPLINAN MENYIKAT GIGI PADA ANAK - Rejeki, Putri; Prasetya, Mia Ayustina; Anggaraeni, Putu Ika; Aprillia, Rika (E-Jurnal Medika Udayana; Vol 12 No 5 (2023): E-Jurnal Medika Udayana, 2023)
Introduction : The behavior of teeth brushing with the correct method in Indonesian people is still relatively low at 2.8%, causing an increase in dental and oral problems from 43.3% in 2007 to 57.6% in 2018. The most dental and oral problems by age are in the age group 5-9 years (51.72%). Efforts to improve children’s behavior in maintaining their dental health require health promotion education with interesting and appropriate methods for children. This study aims to develop "Kartu Petualangan" as a health promotion media to improve the discipline of teeth brushing in children. Method: This Research uses type Research and Development (R&D) study method with eight stages. The steps are potential and problems, data collection, product design, product validation, design revision, product testing, product revision, and usage trial. Result & Discussion: The results of the problems identified through the literature study are used as the basis for product development. Before being tested, the learning media was validated by experts who got results from material experts is 85% and display experts is 80%, they were in the "Eligible" category then revised according to expert input. After that, the product trials in small groups were carried out and got 86% results which were included in the "Very Eligible" category then revised according to input from the product trial questionnaire. Furthermore, the trial for use in a wider group was carried out and obtained 87% results which were included in the "Very Eligible" category. Conclusion: The conclusion of this study is that "Kartu Petualangan" are suitable to be used as a health promotion medium to improve the discipline of teeth brushing in children. Keywords : Health Promotion Media; Reward Stickers; Teeth Brushing